Age and Descriptive Representation in Southern Europe: The Impact of the Great Recession on National Parliaments - Freire, A.; Pedrazzani, A.; Tsatsanis, E.; Coller, X.; Segatti, P. (A Generational Divide? Age-related Aspects of Political Transformation in Post-crisis Southern Europe, 2023)
This chapter looks at how well different age groups are represented in the parliaments of Portugal, Spain, Italy and Greece. We focus on three periods – before, during and after the ‘Great Recession’ – assuming the economic turmoil has generated new demands channelled by new parties that have recently entered parliament or have had a surge during the crisis. Data comes from mass surveys carried out in each country and from MP biographies. The findings reveal relevant changes in Spain and Italy, with more young people in the parties that appeared or had a surge during the crisis, whereas in Greece and Portugal no relevant changes are observed.